Manajemen Pemasaran Kewirausahaan Melalui E-Commerce Untuk Meningkatkan Sebuah Kinerja UMKM - Sudiantini, Dian; Adelia, Liza; Prastiwi, Lusiana; BR Kembaren, Lusitania; Dwi Saiful Qhozi, M (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This globalization era, competition has significantly increased, which makes companies to work hard to ensure their businesses keep visible to the public. This study aims to determine how to manage entrepreneurial marketing through e-commerce to increase MSME performance. This study used descriptive qualitative methods. The results of marketing studies are a series of activities conducted by organizations carried out to satisfy the needs and desires of their customers by creating, offering, and exchanging products and services of value. Marketing will be more effective if marketers understand how marketing activities are carried out. The methodology in this study was based on strategic thinking, which summarized and explained all marketing activities, including production forecasts, pricing, profit targets, sales, and others. The advantages of e-commerce are that it can be utilized by both large and small businesses, allowing anyone to shop easily and quickly from anywhere and anytime. It enables users to navigate websites, search for and retrieve information quickly. Since most SMEs do not have physical locations and operate online, e-commerce is highly necessary to enable SMEs to operate, thereby reducing costs. E-commerce it also allows online businesses to expand their reach without limits and provides a very attractive online sales platform for their customers.